Psychosocial and pharmacologic interventions for problematic methamphetamine use: Findings from a scoping review of the literature. - Mona Hersi; Kim Corace; Candyce Hamel; Leila Esmaeilisaraji; Danielle Rice; Nicole Dryburgh; Becky Skidmore; Gary Garber; Amy Porath; Melanie Willows; Paul MacPherson; Beth Sproule; et al. (PLoS ONE)
Rationale Methamphetamine use and related harms have risen at alarming rates. While several psychosocial and pharmacologic interventions have been described in the literature, there is uncertainty regarding the best approach for the management of methamphetamine use disorder (MUD) and problematic methamphetamine use (PMU). We conducted a scoping review of recent systematic reviews (SR), clinical practice guidelines (CPG), and primary controlled studies of psychosocial and pharmacologic treatments for MUD/PMU. Methods Guided by an a priori protocol, electronic database search updates (e.g., MEDLINE, Embase) were performed in February 2022. Screening was performed following a two-stage process, leveraging artificial intelligence to increase efficiency of title and abstract screening. Studies involving individuals who use methamphetamine, including key subgroups (e.g. those with mental health comorbidities; adolescents/youths; gay, bisexual, and other men who have sex with men) were sought. We examined evidence related to methamphetamine use, relapse, use of other substances, risk behaviors, mental health, harms, and retention. Figures, tables and descriptive synthesis were used to present findings from the identified literature. Results We identified 2 SRs, one CPG, and 54 primary studies reported in 69 publications that met our eligibility criteria. Amongst SRs, one concluded that psychostimulants had no effect on methamphetamine abstinence or treatment retention while the other reported no effect of topiramate on cravings. The CPG strongly recommended psychosocial interventions as well as self-help and family support groups for post-acute management of methamphetamine-related disorders. Amongst primary studies, many interventions were assessed by only single studies; contingency management was the therapy most commonly associated with evidence of potential effectiveness, while bupropion and modafinil were analogously the most common pharmacologic interventions. Nearly all interventions showed signs of potential benefit on at least one methamphetamine-related outcome measure. Discussion This scoping review provides an overview of available interventions for the treatment of MUD/PMU. As most interventions were reported by a single study, the effectiveness of available interventions remains uncertain. Primary studies with longer durations of treatment and follow-up, larger sample sizes, and of special populations are required for conclusive recommendations of best approaches for the treatment of MUD/PMU.